The mitochondrial Ca2+ channel MCU is critical for tumor growth by supporting cell cycle progression and proliferation - Fernandez Garcia, Emily; Paudel, Usha; Noji, Michael C.; Bowman, Caitlyn E.; Rustgi, Anil K.; Pitarresi, Jason R.; Wellen, Kathryn E.; Arany, Zolt; Weissenrieder, Jillian S.; Foskett, J. Kevin (Frontiers in Cell and Developmental Biology, 2023)
The mitochondrial uniporter (MCU) Ca2+ ion channel represents the primary means for Ca2+ uptake into mitochondria. Here we employed in vitro and in vivo models with MCU genetically eliminated to understand how MCU contributes to tumor formation and progression. Transformation of primary fibroblasts in vitro was associated with increased MCU expression, enhanced mitochondrial Ca2+ uptake, suppression of inactivating-phosphorylation of pyruvate dehydrogenase and a modest increase of mitochondrial respiration. Inhibition of mitochondrial Ca2+ uptake by genetic deletion of MCU markedly inhibited growth of HEK293T cells and of transformed fibroblasts in mouse xenograft models. Reduced tumor growth was primarily a result of substantially reduced proliferation and fewer mitotic cells in vivo, and slower cell proliferation in vitro associated with delayed progression through S-phase of the cell cycle. MCU deletion inhibited cancer stem cell-like spheroid formation and cell invasion in vitro, both predictors of metastatic potential. Surprisingly, mitochondrial matrix Ca2+ content and membrane potential, global dehydrogenase activity, respiration and ROS production were unchanged by genetic deletion of MCU in transformed cells. In contrast, MCU deletion elevated glycolysis and glutaminolysis, strongly sensitized cell proliferation to glucose and glutamine limitation, and altered agonist-induced cytoplasmic Ca2+ signals. Our results reveal a dependence of tumorigenesis on MCU, mediated by a reliance on mitochondrial Ca2+ uptake for cell metabolism and Ca2+ dynamics necessary for cell-cycle progression and cell proliferation.